A Qualitative Study in Using the Curriculum Cycle Model and Genre Theory to Improve Students’ Business Negotiation Writing Performance in Chinese University Contexts - Xi, Yihan (Scholar: Human Sciences, 2025)
Purpose: This study investigates the effectiveness of integrating a curriculum cycle model and genre theory to enhance Chinese university students’ proficiency in business English negotiation writing. Research Design, Data, and Methodology: The research employs a qualitative approach to explore the impact of the curriculum cycle model on students’ writing abilities, perceptions, and preferences. After the experiment teaching for 8 weeks, twenty-eight undergraduate students majoring in English at Wuchang University of Technology, Wuhan, China participated in in-person interviews to gather qualitative data. Results: Findings from the interviews revealed that students held positive views regarding the curriculum cycle model, emphasizing its role in enhancing their negotiation writing skills. The study concludes that implementing such pedagogical approaches can significantly benefit students by equipping them with essential negotiation skills and fostering effective communication in business contexts. Conclusions: This research contributes to the field by demonstrating how innovative teaching methodologies can empower students to navigate and succeed in the complexities of professional communication.